2009
DOI: 10.1159/000250437
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor-9 Agonist Inhibits Airway Inflammation, Remodeling and Hyperreactivity in Mice Exposed to Chronic Environmental Tobacco Smoke and Allergen

Abstract: er, and AHR. The reduced airway remodeling in mice treated with the TLR-9 agonist was associated with significantly reduced numbers of peribronchial MBP+ and peribronchial TGF-␤ 1 + cells, and with significantly reduced levels of lung Th2 cytokines [interleukin-5 and interleukin-13] and TGF-␤ 1 .Conclusion: These studies demonstrate that TLR-9-based therapies inhibit airway inflammation, remodeling and AHR in mice coexposed to ETS and allergen who exhibit enhanced airway inflammation and remodeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 81 publications
0
12
1
Order By: Relevance
“…Some data suggest that Toll-like receptor expression and function in cigarette smoking are causally linked to COX and NADPH activation, oxidative stress, and damage, 60 whereas other results show that the activation of Toll-like receptor-9 by stimulation with an agonist reduces lung inflammation in response to secondhand smoke. 61 Several experimental studies demonstrated that, apart from causing vascular endothelial dysfunction, cigarette smoke causes physical damage to the vascular endothelium (Figure). In essence, 2 forms of damage were observed: (1) contraction of endothelial cells, mediated by oxidation and collapse of the tubulin system, which is reversible and may be part of the clinical symptoms of smoking-caused reduction of FMD, 57 and (2) endothelial cell death.…”
Section: Arterioscler Thromb Vasc Biol March 2014mentioning
confidence: 99%
“…Some data suggest that Toll-like receptor expression and function in cigarette smoking are causally linked to COX and NADPH activation, oxidative stress, and damage, 60 whereas other results show that the activation of Toll-like receptor-9 by stimulation with an agonist reduces lung inflammation in response to secondhand smoke. 61 Several experimental studies demonstrated that, apart from causing vascular endothelial dysfunction, cigarette smoke causes physical damage to the vascular endothelium (Figure). In essence, 2 forms of damage were observed: (1) contraction of endothelial cells, mediated by oxidation and collapse of the tubulin system, which is reversible and may be part of the clinical symptoms of smoking-caused reduction of FMD, 57 and (2) endothelial cell death.…”
Section: Arterioscler Thromb Vasc Biol March 2014mentioning
confidence: 99%
“…Recent publications in mice have shown that tCS exposure can on the one hand enhance allergic sensitization and the allergic pulmonary Th2 response [15][16][17][18][19]. Recent publications in mice have shown that tCS exposure can on the one hand enhance allergic sensitization and the allergic pulmonary Th2 response [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…So far, specific allergen immunotherapy (SIT) represents the only ‘etiologic' treatment that directs towards the basis of atopic respiratory disease and influences the natural history of AR and asthma [3]. To develop safer and more efficacious allergy vaccines or novel stand-alone therapeutics, innate immunity stands out as a major target since it is the first line of defense [4,5]. Innate immunity enables initial recognition of invading pathogens and presents them to the immune system to elicit an appropriate adaptive immune response.…”
Section: Introductionmentioning
confidence: 99%